VISI, MISI ORGANISASI, MANAJEMEN PENGETAHUAN DAN INOVASI PADA ANARA HOTEL BANDARA SOEKARNO HATTA DI TANGERANG - PRASASTYO, KLEMENS WEDANAJI; SURYAWAN, IAN NURPATRIA; RUDYANTO, ASTRID (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2024)
Vision and mission are important for organizations in determining the goals of the organization, because vision is an important element in the organization because it is part of strategic planning. Innovation is a view that assumes that organizations use ideas and external and internal paths, by having good knowledge, they can make good innovations. The training conducted at the Anara Airport Hotel Bandara Soekarno Hatta uses a case study approach on how to create a good vision and mission. Evidently, by following the training provided by the instructors, the participants understand and comprehend how to create a good vision and mission and how to work in a compact team in order to create good synergy in order to achieve good organizational goals.